HOLISTIC PERSPECTIVE ON ENVIRONMENTAL CAPITAL AND POLITICAL CAPITAL IN SOUTHEAST ASIA - Bhimo Rizky Samudro; Yogi Pasca Pratama; Albertus Magnus Soesilo (Journal of Applied Economics in Developing Countries, 2018)
This paper surveys the relationship between environmental capital and political capital among countries in Southeast Asia using holistic perspective. Holistic theories emphasize that the whole is not only greater than the sum of the parts, but that the parts are related in such way that their functioning is conditioned by their relationship. Holistic perspective is being supported by the ecological footprint data as environmental capital among countries in Southeast Asia. Then, this paper uses political capital among countries in that region. Political capital can be derived into some political indicators such as political rights and civil liberties. Next, the paper examines the pattern relationship between these variables environmental capital and political capital in Southeast Asia. Change in these forms of capital represent “institutional relationship” among countries in Southeast Asia. By accomplishing the concept “institutional relationship”, this paper can explain various responses among countries in Southeast Asia for responding uncertainty condition around those capitals.Keywords: Southeast Asia, Environmental Capital, Political Capital, Holistic Perspective